THE ROLE OF COOPERATIVE LEARNING METHOD IN TEACHING AND SUPPORTING CHILDREN WITH DIVERSE NEEDS - Talapova A.K.; Yuldasheva A.K. (Progress in Science, 2025)
This study investigates the effectiveness of cooperative learning as a pedagogical approach for supporting children with diverse educational needs in inclusive classroom environments. Grounded in social constructivist and sociocultural theories, cooperative learning emphasizes collaboration, shared responsibility, and peer support to enhance both academic and social outcomes. The research involved forty teachers who participated in a professional conference on cooperative learning methods. Following the event, participants completed a structured questionnaire consisting of fifteen Likert-scale items and five open-ended questions to assess their perceptions, experiences, and challenges in implementing cooperative learning strategies. Quantitative results indicated strong agreement regarding the method’s positive impact on student motivation, academic achievement, and social inclusion. Qualitative thematic analysis revealed three key themes: improved social engagement, challenges in managing group dynamics, and the need for continuous professional development. The findings suggest that cooperative learning fosters inclusion and student engagement when supported by proper teacher training and structured implementation.